Liver cirrhosis in 2021: Global Burden of Disease study - Hong Duo; Jian You; Siqi Du; Mengran Yu; Shaomei Wu; Pengpeng Yue; Xiao Cui; Yihui Huang; Jun Luo; Huaqin Pan; Qifa Ye (PLoS ONE, 2025)
Background Liver cirrhosis is a chronic progressive disease caused by various liver injury mechanisms, characterized by irreversible fibrosis, hepatocyte degeneration and necrosis, and the formation of regenerative nodules, ultimately leading to liver failure and multiple severe complications, significantly increasing the risk of mortality. Methods This study analyzes global and China-specific trends in liver cirrhosis incidence, prevalence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021, focusing on various causes including hepatitis B virus (HBV), hepatitis C virus (HCV), alcoholic liver disease, and non-alcoholic fatty liver disease (NAFLD). Data from the Global Burden of Disease (GBD) database were used to assess changes in liver cirrhosis statistics globally and in China. The study examined incidence, prevalence, mortality, and DALYs over the period from 1990 to 2021. Results Global liver cirrhosis incidence reached 58.4 million in 2021, up from 36.9 million in 1990, primarily driven by NAFLD, which increased from 24.8 million in 1990 to 48.3 million in 2021. While HBV- and HCV-related cirrhosis declined, deaths from alcoholic cirrhosis rose. In China, NAFLD became the main cause, although alcohol-related cirrhosis and an aging population remain major challenges. Conclusions The growth of NAFLD and alcohol-related cirrhosis undermines progress in controlling HBV and HCV. Targeted prevention and management strategies are needed, especially in regions with low and middle SDI, which show higher cirrhosis mortality. For China, early intervention for NAFLD and continued control of HBV and HCV are critical to reduce the cirrhosis burden.